Resveratrol Alleviates the KCl Salinity Stress of Malus hupehensis Rhed - Li, Tingting; Li, Yuqi; Sun, Zhijuan; Xi, Xiangli; Sha, Guangli; Ma, Changqing; Tian, Yike; Wang, Caihong; Zheng, Xiaodong (Frontiers in Plant Science, 2021)
Applying large amounts of potash fertilizer in apple orchards for high apple quality and yield aggravates KCl stress. As a phytoalexin, resveratrol (Res) participates in plant resistance to biotic stress. However, its role in relation to KCl stress have never been reported. Herein, we investigated the role of Res in KCl stress response of Malus hupehensis Rehd., a widely used apple rootstock in China and sensitive to KCl stress. KCl-stressed apple seedlings showed significant wilting phenotype and decline in photosynthetic rate, and the application of 100 µmol Res alleviated KCl stress and maintained photosynthetic capacity. Exogenous Res can strengthen the activities of POD and CAT thus eliminate the reactive oxygen species (ROS) production induced by KCl stress. Moreover, exogenous Res can decrease the electrolyte leakage by accumulating proline for osmotic balance under KCl stress. Furthermore, exogenous Res application can affect K+/Na+ homeostasis in cytoplasm by enhancing K+ efflux outside the cells, inhibiting Na+ efflux and K+ absorption, and compartmentalizing K+ into vacuoles through regulating the expression of K+ and Na+ transporter genes. These findings provide a theoretical basis for the application of exogenous Res to relieve the KCl stress of apples.